'Memory is so different now': the translation and circulation of Inuit-Canadian literature in English and French*. (3rd April 2017) - Henitiuk, Valerie
ABSTRACT: Inuit, even more marginalized than the First Nations or Métis, settled along what is now northern Canada some 4000–6000 years ago. They have a centuries-long history of orature (legends, myths, songs, etc.), although literacy is a more recent arrival. Interest in this traditionally nomadic, socially complex, and richly imaginative culture has been increasing rapidly in the past few years, with the emergence of prize-winning films by Zacharias Kunuk and others; the second edition of Life Among the Qallunaat (the autobiography of Mini Freeman, a quadrilingual Inuk who worked as a translator in Ottawa for some 20 years); and the publication in 2013 of an English version of what has been called the first Inuktitut novel, first begun by a woman in the 1950s. This paper will examine a few recent developments in the present-day circulation of the traditions of one Canada's no-longer-quite-so-invisible 'invisible minorities, ' with a particular focus on Sanaaq by Mitiarjuk Nappaaluk, who has been referred to as 'the accidental Inuit novelist' (Martin, 2014 ).